Estudio de pre- factibilidad para la creación de una empresa productora y comercializadora de anti-pasto en la ciudad de Santa Marta (2020)
The research is documented with fundamental information, which supports the study and feasibility of producing and marketing Antipasto in Santa Marta. It is worth mentioning that said research has a market study aimed at finding the target market, and its potential consumers of Antipasto, the marketing plan, where programs will be created to cover key aspects of the product, and human resources will also be analyzed. , physical and supplies, in the fourth stage the necessary documents for the constitution of the company are explained, at the end, the costs, sale price, financial evaluation, the recovery period of said investment, and the cost-benefit are shown of the project.